Preparation and characterization of Cu(II)-N-salicylideneanthranilic acids, their reduction products and hydrolysis of the Schiff base - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1996)
Copper (II) complexes of N-salicylideneanthranilic acid (I) and its derivatives (LI, III) as well as their NaBH4 reduction products, namely N-(2-hydroxybenzyl) anthranilic acids (IV-VI) have been prepared and their structures have been determined analytically Tetracoordinated planar structures of the Cu(II) complexes of the Schiff bases and distorted tetrahedral structures of the Cu(II) complexes of compounds V-VI have been elucidated by ESR and other spectral methods. During the preparation of the complex the hydrolysis of the Schiff base often takes place in the presence of water giving anthranilates and salicylaldehydates of metals to some extent along with the complexes of the Schiff base. The kinetic data for the hydrolysis of N-salicylideneanthranilic acid (I) in methanol-water solution also are reported.
Keywords: N-salicylideneanthranilic acids; reduction; hydrolysis; stability; Cu(II) complexes